“A creature inside me”: perceptions and representations of HIV among adolescents living with HIV in Malawi - Nadine Ammon; Mark Limmer; Alex Kaley (AIDS Research and Therapy)
Abstract Malawi is among the countries with the highest HIV prevalence worldwide. Adolescents living with HIV (ALHIV) face diverse challenges, which influence their emotional wellbeing and long-term health, in addition to impacting HIV onward transmission. HIV education, especially the use of fear-based animation, but also the figurative language used for HIV, contribute to how ALHIV perceive and respond to their HIV status. The aim of the study was to explore how ALHIV in Malawi describe, perceive, and represent HIV, with a particular focus on the role of language in shaping these perceptions and its impact on their experiences and emotional wellbeing. This study employed hermeneutic phenomenology and reflexive thematic analysis; data were collected through semi-structured in-depth interviews, focus group discussions and drawings. Participants were sampled purposively and included 16 ALHIV and five service providers. The adolescents imagined HIV as personified, harmful creature in their body with functional senses and gender identity. Those negative perceptions originated mainly from the local term used for HIV, HIV-related stigma and discrimination and HIV representations in hospital HIV books. HIV peer support groups were identified as safe environments for learning about HIV and for debating HIV-related topics, especially in view of the usually required silence and secrecy to prevent stigma. The findings enhance the understanding of participants’ lived experiences and perceptions of HIV, and thus may contribute to new methods of holistic health education, tailored for adolescents to improve their emotional wellbeing and attitudes towards HIV through context-specific programmes.